Non-peripherally tetra substituted phthalocyanines bearing benzodioxane moieties: Synthesis, characterization and investigation of electrochemical and spectroelectrochemical properties - KOCA, ATIF (ELSEVIER SCIENCE BV, 2019)
The 1,4-benzodioxane substituted phthalonitrile compound (3) and non-peripherally tetra substituted cobalt(II) (4), nickel(II) (5) and copper(II) (6) phthalocyanine complexes were synthesized. The structural characterization of the compounds was performed by using various spectroscopic techniques. The electron transfer properties of the phthalocyanine complexes (4-6) were investigated by voltammetric and in situ spectroelectrochemical measurements. The electrochemical and spectroelectrochemical properties of the non-peripherally tetra substituted metallo-phthalocyanines (4-6) having redox active and inactive metal center were compared with each other in terms of electrochemical responses and the differences were revealed. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; 1,4-Benzodioxane; Electrochemistry; Spectroelectrochemistry; HYDROGEN EVOLUTION REACTION; OXYGEN REDUCTION; METAL-FREE; ZINC(II); COBALT; CO(II); FILMS